2022
DOI: 10.1021/acs.est.2c02113
|View full text |Cite
|
Sign up to set email alerts
|

Pentavalent Uranium Incorporated in the Structure of Proterozoic Hematite

Abstract: Characterizing the chemical state and physical disposition of uranium that has persisted over geologic time scales is key for modeling the long-term geologic sequestration of nuclear waste, accurate uranium–lead dating, and the use of uranium isotopes as paleo redox proxies. X-ray absorption spectroscopy coupled with molecular dynamics modeling demonstrated that pentavalent uranium is incorporated in the structure of 1.6 billion year old hematite (α-Fe2O3), attesting to the robustness of Fe oxides as waste for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Experimental evidence for U(V) persistence in iron oxides has been accumulating for more than 10 years . The most recent work has evidenced the presence of U(V) in a 1.6 billion years old hematite . Previous work has both reported the persistence of U(V) up to 4 days as well as the formation of transient nanowires composed of individual uranium oxide nanoparticles that later collapse into UO 2 nanoclusters .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental evidence for U(V) persistence in iron oxides has been accumulating for more than 10 years . The most recent work has evidenced the presence of U(V) in a 1.6 billion years old hematite . Previous work has both reported the persistence of U(V) up to 4 days as well as the formation of transient nanowires composed of individual uranium oxide nanoparticles that later collapse into UO 2 nanoclusters .…”
Section: Discussionmentioning
confidence: 99%
“…Due to its redox sensitivity and long residence time in the ocean (∼500 ky), U is considered as a reliable paleo-redox tracer to reconstruct Earth’s past atmosphere and oceans as well as a monitoring tool to trace U(VI) reduction in the modern environments. While the current understanding is grounded in the isotope fractionation that occurs during the transition from U(VI) to U(IV), the existence of U(V) and its role in the fractionation processes have been largely overlooked. In light of the identification of U(V) in 1.6 billion years old hematite, it is increasingly clear that U isotope fractionation during Fe(II)-mediated reduction must consider intermediate valence states and their attendant fractionation behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these ligands are promising candidates for the stabilization of U(V), and recent studies have suggested that dpa could stabilize U(V) in aqueous solution. 50,51 Very little is known about the distribution of U(V) in the environment, even though it was identified in the matrix of a 1.6 billion year-old hematite by Ilton et al, 52 opening the door to a quest for U(V) in the environment. Indeed, U(V) chemistry and its resulting stability is dependent on the local chemical environment: available organic carbon, presence of mineral phases, physical state of U (solid/aqueous), pH, electrochemical potential, and O 2 levels.…”
Section: ■ Environmental Relevancementioning
confidence: 99%
“…Similarly, soddyite, uranophane, boltwoodite, and sklodowskite are formed by the oxidation of uraninite (UO 2 ) in nature. , In the natural environment, the most stable oxidation states of uranium are U­(IV) and U­(VI), and the latter dominates in many crystalline minerals . In contrast, the fact that U­(V) species in aqueous solution is easily oxidized to uranium­(VI) or disproportionates into U­(IV) and U­(VI) species rapidly makes it rarely observed in naturally occurring minerals. , The exploration of new uranium silicate compounds under extreme conditions in the laboratory leads to the creation of many new phases of uranium silicate with different kinds of structural units. For example, Lii and co-workers have reported hydrothermal syntheses of a U­(IV) silicate, Cs 2 U IV Si 6 O 15 , two U­(V) silicates, K­(U V O)­Si 2 O 6 and K 3 (U V 3 O 6 )­(Si 2 O 7 ), and several mixed-valence uranium silicates, including [Na 9 F 2 ]­[(U V O 2 )­(U VI O 2 ) 2 (Si 2 O 7 ) 2 ], Na 7 U IV O 2 (U V O) 2 (U V/VI O 2 ) 2 SiO 6 , and Cs 4 (U V O)­(U IV/V O) 2 (Si 2 O 7 ) 2 .…”
Section: Introductionmentioning
confidence: 99%